New Deal Policies and the Persistence of the Great Depression: A General Equilibrium Analysis - Cole, Harold L.; Ohanian, Lee E. (Journal of Political Economy, 2004)
There are two striking aspects of the recovery from the Great Depression in the United States: the recovery was very weak, and real wages in several sectors rose significantly above trend. These data contrast sharply with neoclassical theory, which predicts a strong recovery with low real wages. We evaluate the contribution to the persistence of the Depression of New Deal cartelization policies designed to limit competition and increase labor bargaining power. We develop a model of the bargaining process between labor and firms that occurred with these policies and embed that model within a multisector dynamic general equilibrium model. We find that New Deal cartelization policies are an important factor in accounting for the failure of the economy to recover back to trend.